Improving Windowed Decoding of SC LDPC Codes by Effective Decoding Termination, Message Reuse, and Amplification - Inayat Ali; Jong-Hwan Kim; Sang-Hyo Kim; Heeyoul Kwak; Jong-Seon No (IEEE Access)
In this paper, we address a number of weaknesses of the windowed decoding of spatially coupled low-density parity-check (SC LDPC) codes and propose three modifications that simultaneously improve its performance, complexity, and latency. An effective termination method of the windowed decoding and the reuse of edge messages of previous target symbols provide a good performance-latency tradeoff when compared with the conventional windowed decoder. Also, we propose a scheme that lowers the error floor, in which the amplified edge messages of the previous window are used in the present window. The proposed windowed decoding, consisting of the three schemes, provides a significant performance gain with smaller latency. The validity of the new windowed decoding is verified by the evaluation with codes from different SC LDPC ensembles.